Perlindungan Platform Halodoc Dalam Menjaga Kerahasiaan Data Pengguna - Simanjuntak , Dwi Amanda; Nasution, Irwan Padli (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
The purpose of this article is to investigate the methods used by the Halodoc platform in protecting user data during doctor consultations. To collect information, the author uses a literature review approach, collecting and examining various literature, books, scientific papers, as well as data from the media and other related sources. The findings show that Halodoc implements an oath-taking process for medical and non-medical staff to ensure the confidentiality of user data. even non-medical staff also take the oath as they are part of the Halodoc integrated health care unit which is responsible for the personal information and health status of patients in the hospital